Assessment of the Energy Efficiency and Cost of Low-Income Housing Based on BIM Considering Material Properties and Energy Modeling in a Tropical Climate - Vicente Macas-Espinosa; Israel Portilla-Sanchez; David Gomez; Ruben Hidalgo-Leon; Julio Barzola-Monteses; Guillermo Soriano (Energies)
This work analyzes the potential impact of thirteen passive and active factors on a low-income housing (LIH) model in a tropical climate. For this purpose, a study of material properties and energy modeling using Building Information Modelling (BIM) is carried out, which helps to evaluate these factors’ energetic and economic implications. Two significant assessments are highlighted, namely active and passive factor analysis and dominant factor analysis. The research studied the architectural design of a one-story house measuring thirty-six square meters outlined by the Ecuadorian Construction Standard (NEC) chapter 15 part 4. A 3D architectural model was generated using Revit 2024 simulation software and subsequently employed to establish an energy model used in Autodesk Insight Software 2024 to assess the factors influencing energy consumption and annual energy expenses. The analysis included a comparison with a model of the house based on the ASHRAE 90.2 standard. The active and passive factors were ranked according to their impact on energy efficiency in the model. The results show that Energy Use Intensity (EUI) has a higher reduction for the ASHRAE model of 4.63%, with 21.60% for the Energy cost. The active factors exhibited a greater impact on the energy performance of the LIH than the passive factors, with the PV-Surface coverage being the factor that generated the highest EUI reduction, with 39.66% and 78.51% for both models. The study concluded by emphasizing the importance of adopting active strategies to achieve energy efficiency and economical house design.